Transposable Elements versus the Fungal Genome: Impact on Whole-Genome Architecture and Transcriptional Profiles - Castanera, Raúl; López-Varas, Leticia; Borgognone, Alessandra; LaButti, Kurt; Lapidus, Alla; Schmutz, Jeremy; Grimwood, Jane; Pérez, Gúmer; Pisabarro, Antonio G.; Grigoriev, Igor V.; Stajich, Jason E.; Ramírez, Lucía (PLoS genetics, 2016)
Transposable elements (TEs) are exceptional contributors to eukaryotic genome diversity. Their ubiquitous presence impacts the genomes of nearly all species and mediates genome evolution by causing mutations and chromosomal rearrangements and by modulating gene expression. We performed an exhaustive analysis of the TE content in 18 fungal genomes, including strains of the same species and species of the same genera. Our results depicted a scenario of exceptional variability, with species having 0.02 to 29.8% of their genome consisting of transposable elements. A detailed analysis performed on two strains of Pleurotus ostreatus uncovered a genome that is populated mainly by Class I elements, especially LTR-retrotransposons amplified in recent bursts from 0 to 2 million years (My) ago. The preferential accumulation of TEs in clusters led to the presence of genomic regions that lacked intra- and inter-specific conservation. In addition, we investigated the effect of TE insertions on the expression of their nearby upstream and downstream genes. Our results showed that an important number of genes under TE influence are significantly repressed, with stronger repression when genes are localized within transposon clusters. Our transcriptional analysis performed in four additional fungal models revealed that this TE-mediated silencing was present only in species with active cytosine methylation machinery. We hypothesize that this phenomenon is related to epigenetic defense mechanisms that are aimed to suppress TE expression and control their proliferation.